2009
DOI: 10.1002/jrs.2497
|View full text |Cite
|
Sign up to set email alerts
|

Raman investigations of rare‐earth arsenate single crystals

Abstract: Polarized Raman spectroscopy was used to investigate the room-temperature phonon characteristics of a series of rare-earth arsenate (REAsO 4 , RE = Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu) single crystals. The Raman data were interpreted in a systematic manner based on the known tetragonal zircon structure of these compounds, and assignments and correlations were made for the observed bands. We found that the wavenumbers of the internal modes of the AsO 4 tetrahedron increased with increasing atomic number. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In fact, a thorough description of the vibrational dynamics of the prototype compound of orthovanadate family with zircon-type structure is provided in our present work, by showing reliable experimental evidences of some Raman modes, which were either not reported in the existing literature [18][19][20][21] or wrongly assigned in wave number. 23 In particular, the difficult detection of the systematically missing E g (4) mode, which is characterized by an extremely weak intensity, fully confirms the correctness of the hypothesis formulated by Elliott et al 20 On the other hand, what is also more important, by comparison with the compounds of the orthophosphate family 28,45,46 and rare-earth arsenates 47 with the same zircon-type structure, we can infer that, as far as the other compounds of this orthovanadate family are considered, the frequency of this E g mode should be nearly independent of the rare-earth ion mass, and, therefore, that it should occurs close nearby at the same frequency as it is observed in YVO 4 . Moreover, the highly symmetry-selective measurements of this study point out the added value of our experimental approach based on the use of a micromanipulator to properly orientate the sample.…”
Section: Discussionsupporting
confidence: 64%
“…In fact, a thorough description of the vibrational dynamics of the prototype compound of orthovanadate family with zircon-type structure is provided in our present work, by showing reliable experimental evidences of some Raman modes, which were either not reported in the existing literature [18][19][20][21] or wrongly assigned in wave number. 23 In particular, the difficult detection of the systematically missing E g (4) mode, which is characterized by an extremely weak intensity, fully confirms the correctness of the hypothesis formulated by Elliott et al 20 On the other hand, what is also more important, by comparison with the compounds of the orthophosphate family 28,45,46 and rare-earth arsenates 47 with the same zircon-type structure, we can infer that, as far as the other compounds of this orthovanadate family are considered, the frequency of this E g mode should be nearly independent of the rare-earth ion mass, and, therefore, that it should occurs close nearby at the same frequency as it is observed in YVO 4 . Moreover, the highly symmetry-selective measurements of this study point out the added value of our experimental approach based on the use of a micromanipulator to properly orientate the sample.…”
Section: Discussionsupporting
confidence: 64%
“…The three high-frequency internal modes (E g , B 1g , and A 1g ) are the only three modes not following exactly this systematic behavior. 20 Apparently, the frequency change could be related to changes in X-O bond lengths as proposed by Podor [60] as observed in rare-earth arsenates, vanadates, and phosphates [61]. Another interesting feature to discuss is the remarkable differences of the symmetric stretching mode ( 1 ), the A 1g mode with higher wavelength, and the antisymmetric stretching modes ( Table II).…”
Section: B Raman-active Phonons In the Zircon Structurementioning
confidence: 64%
“…Polarized Raman spectroscopy was used by Barros et al . to investigate the room‐temperature phonon characteristics of a series of rare‐earth arsenate (REAsO 4 , RE═Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb and Lu) single crystals . It was found that the wavenumbers of the internal modes of the AsO 4 tetrahedron increased with increasing atomic number.…”
Section: Solid‐state Studiesmentioning
confidence: 99%